2021
DOI: 10.23887/jeu.v9i2.41036
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Pengembangan Modul Berbasis Proyek pada Mata Kuliah Kewirausahaan Akademi Komunitas Negeri Pesisir Selatan

Abstract: Belum tersedianya modul yang sistematis pada mata kuliah Kewirausahaan di Program Studi Teknik Fabrikasi dan Pengelasan Logam (TFPL) serta hasil belajar peserta didik belum optimal. Penelitian ini bertujuan untuk mengembangkan modul pembelajaran dan menghasilkan modul yang valid, praktis dan efektif pada mata kuliah Kewirausahaan berbasis proyek untuk peserta didik Program Studi TFPL di Akademi Komunitas Negeri Pesisir Selatan. Penelitian ini menggunakan metode Research and Development (penelitian dan pengemba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…In line with research says that teaching materials that are well developed using a fairly good approach method, students will be active so that increased understanding of knowledge and skills possessed because the problems given are directly related to the conditions in the field (Natalia & Jalinus, 2021;Putra et al, 2022;Syah et al, 2019). In line with research, regarding the effectiveness of developing teaching materials, it was found that the development of innovative teaching materials will make students more open and creative in learning (Hsin & Wu, 2023;Mirah Setia Dewi et al, 2019;Pursitasari et al, 2022).…”
Section: Discussionmentioning
confidence: 84%
“…In line with research says that teaching materials that are well developed using a fairly good approach method, students will be active so that increased understanding of knowledge and skills possessed because the problems given are directly related to the conditions in the field (Natalia & Jalinus, 2021;Putra et al, 2022;Syah et al, 2019). In line with research, regarding the effectiveness of developing teaching materials, it was found that the development of innovative teaching materials will make students more open and creative in learning (Hsin & Wu, 2023;Mirah Setia Dewi et al, 2019;Pursitasari et al, 2022).…”
Section: Discussionmentioning
confidence: 84%
“…Dibalik pendapat di atas ada juga pendapat yang bertolak belakang dengan pendapat sebelumnya yang mengatakan bahwa kewirausahaan adalah sebuah ilmu yang bisa dipelajari oleh seseorang melalui sebuah lembaga-lembaga pendidikan atau institusi, dan bahkan bisa dipelajari dari mana saja bahkan dari pengalaman orang lain. Belajar berwirausaha adalah hal yang sangat penting, Belajar di pendidikan wirausaha tidak hanya memberikan pekerjaan untuk seseorang, tapi bisa juga seseorang wirausaha menghasilkan lapangan pekerjaan untuk orang lain dan akan meningkatkan perekonomian negara dan perekonomian pelaku usaha itu sendiri (Natalia & Jalinus, 2021).…”
Section: Pendahuluanunclassified